Factors in the success of Western entrepreneurs in the vegetable trade - VATTHANA, Mongkhoun; RITTIBOONCHAI, Wisit; U- THAIRATANA, Pichaya; PUKSOR, Kittiyanee; YOOKU, Amontape (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The purposes of this research are to 1. Compare the success of Western entrepreneurs in the vegetable trade when classified by personal factors; and. 2. Study the factors that influence the success of the vegetable trade of entrepreneurs in the western region from labor, investment, goods, and marketing support. The researcher collected data from 100 vegetable traders in the western region, namely Nakhon Pathom, Kanchanaburi, Phetchaburi, and Ratchaburi provinces, 100 each by quota randomization. The statistics used in data analysis consisted of percentage, mean, standard deviation, t-test, one-way analysis of variance, and multiple regression analysis. The research results showed that: 1. The success of entrepreneurs in the vegetable trade in the West varies according to age, status, education level, income, length of business, and region. 2. The factors that influence the success of the vegetable trade of entrepreneurs in the western region are due to labor, investment, goods, and marketing support. Statistically significant. The multiple regression analysis equations is; The success of the vegetable trade of entrepreneurs in the western region (Y) = 0.77 + 0.13 labor (X1) ** + 0.17 investment (X2) ** + 0.18 goods (X3) **+ 0. 35 marketing support (X4) ** With the prediction accuracy of the said equation at 60 percent.